(untitled) (Heritage, 2022)
The aim of the paper is to present the development of librarianship in Serbia in the period after the Second World War until today, in the period when there is a sudden professionalization and when librarianship through institutionalized education grows into a recognized social аnd humanities science. Based on the hitherto insufficiently known and little used archival material, the development of professional and competent staff in Serbia is highlighted as a precondition for the development of library science. It was noticed that in the period under review, librarianship developed rapidly. Special merits for that initially belong to the Serbian Library Association, and then to the Department for Librarianship and Information Science at the Faculty of Philology, University of Belgrade. The paper combines both historical and current efforts to improve librarianship and to keep up with the sciences of postmodern society.